Fine mapping genetic determinants of the highly variably expressed MHC gene ZFP57. - Plant, K; Fairfax, B; Makino, S; Vandiedonck, C; Radhakrishnan, J; Knight, J (2014)
ZFP57 is an important transcriptional regulator involved in DNA methylation and genomic imprinting during development. Here we demonstrate that gene expression also occurs at a low level in adult peripheral blood cells and other tissues including the kidney and thymus, but is critically dependent on underlying local genetic variation within the MHC. We resolve a highly significant expression quantitative trait locus for ZFP57 involving single-nucleotide polymorphisms (SNPs) in the first intron of the gene co-localizing with a DNase I hypersensitive site and evidence of CTCF recruitment. These data identify ZFP57 as a candidate gene underlying reported MHC disease associations, notably for putative regulatory variants associated with cancer and HIV-1. The work highlights the role that ZFP57 may play in DNA methylation and epigenetic regulation beyond early development into adult life dependent on genetic background, with important potential implications for disease.